Study on the changes of extracellular vesicle content of platelets at different storage periods, storage lesion and clinical efficacy - DING Fang; HAN Xiuhua; LI Xiaoming; LU Ping (Zhongguo shuxue zazhi, 2024)
[Objective] To analyze the changes of platelet extracellular vesicles (PEVs) content in apheresis at different storage periods, track the PEVs and transfusion efficacy of patients, and explore the mechanism of PEVs in relation to platelet storage damage and transfusion efficacy. [Methods] From November 2022 to April 2024, a total of 85 apheresis platelets samples were collected at Jiading District Blood Station. Flow cytometry was used to detect the content of PEVs on the day of collection and before transfusion. The changes in the content of PEVs stored for 1 to 5 days were observed. Patients with acute leukemia were selected as transfusion recipients, and their content of platelet count and PEVs before transfusion and within 24 hours after transfusion, and the efficacy were tracked to explore the mechanism of PEVs in relation to storage lesion and transfusion efficacy. [Results] The content of PEVs before platelet infusion (8.73±4.84) was significantly higher than that on the day of platelet collection (5.11±3.33), and the difference was statistically significant (P<0.01). The increase in the content of PEVs in storage for 2 to 5 days was 2.55±1.38, 3.49±2.63, 3.86±3.55 and 4.50±3.91, with statistically significant difference (P<0.05). The PEVs content in patients after blood transfusion was positively correlated with that before transfusion and that in apheresis platelet bags during transfusion (P<0.001) A total of 85 cases of apheresis platelet transfusion were conducted, with 61 effective transfusions having a CCI value of (13.43±4.70), and 24 transfusion refractoriness cases having a CCI value of (2.27±3.67), showing a statistically significant difference (P<0.001). The transfusion effectiveness rates for patients receiving different storage periods of apheresis platelets of 2 to 5 days were 88.89%, 68.42%, 68.18% and 57.14% respectively, with corresponding CCI values of 11.18±6.10, 10.43±6.77, 9.53±6.75 and 9.48±8.86, and there was no significant difference between CCI groups (P>0.05). There was no significant correlation between the PEVs content before and after transfusion and the efficacy of CCI (P>0.05). There was no significant correlation between the PEVs content before apheresis platelet transfusion and the efficacy of CCI (P>0.05). [Conclusion] The content of PEVs increased with the prolongation of storage time, which could be used as a potential blood quality evaluation and monitoring index during the storage period, but it was not significantly correlated with the efficacy of CCI in transfusion.